Second record of the West African hairy bush viper Atheris hirsuta Ernst & Rödel, 2002 (Serpentes: Viperidae) - Penner, Johannes; Gonwouo, Legrand Nono; Rödel, Mark-Oliver (Zootaxa, 2013)
The African bush vipers of the genus Atheris Cope, 1862 currently comprises 15 species, this includes A. barbouri Loveridge, 1930 (often assigned to the genus Adenorhinos; but see Lenk et al. 2001). All species occur exclusively on the African continent with most species occurring in East and Central Africa. West Africa, defined as the eco-region including Nigeria and all countries westwards, excluding Cameroon (see Penner et al. 2011), currently harbours three species of Atheris. (i) Atheris squamigera (Hallowell, 1854) which has a wide range across Central Africa and can be found in south-eastern Nigeria (Spawls & Branch 1995; Luiselli et al. 2000). However, the taxonomy of central African Atheris is still under debate and several hidden species might be included (see Broadley 1998; Lawson 1999; Lawson & Ustach 2000; Lawson et al. 2001). Concerning distribution,we follow Chippaux (2006) and others in regarding all records of A. squamigera west of Nigeria as doubtful. A true West African species is (ii) Atheris chlorechis (Pel, 1851) which ranges from Guinea, through Sierra Leone, Liberia, Côte d’Ivoire and Ghana to Togo. Its occurrence in Nigeria is unclear. So far no records exist for Benin (Ullenbruch et al. 2010; Hughes 2013; C. Toudonou pers. comm.). The third species, (iii) Atheris hirsuta Ernst & Rödel, 2002, was described from a single specimen found near the ecological research station in the Taï National Park, Côte d’Ivoire. No further records existed until this study.